Perlindugan Hukum Bagi Perempuan Terhadap Kekerasan Seksual Di Indonesia - Nadiavega; Reva Prisslia Dwi Prastianti Lubis; Neizella Gustriani (GLOBAL SCIENTS PUBLISHER, 2025)
Sexual violence is an act that harms a person physically, psychologically, and emotionally, usually occurring in the context of an imbalance of power. Women are a group that is highly vulnerable to forms of sexual violence, including harassment, rape, sexual exploitation, and gender-based violence. In society, women are often perceived as weak and powerless (Faisal et al., 2023). Sexual violence is an act that harms a person physically, psychologically, and emotionally, often occurring in the context of an imbalance of power. Criminal law plays a crucial role in handling cases of sexual violence, by providing punishment for perpetrators and protection for victims. Referring to Article 1, number 1 of Law Number 12 of 2022 (the TPKS Law), the crime of sexual violence is any act that fulfills the elements of a criminal offense as regulated. This research uses a normative juridical approach with statutory regulations. This study examines the impact of sexual violence on women, the factors influencing it, and the forms of legal protection available. In this context, women are vulnerable to various forms of sexual violence.